Film Cooling Effectiveness Data for Simple Injection Geometries: A Collection of Three-Axis Plots - L. D. Stone; R. J. Goldstein (International Journal of Rotating Machinery)
A three-axis plot of laterally averaged film cooling effectiveness versus blowing rate and versus dimensionless distance downstream is a sufficiently compact representation of film cooling effectiveness data for injection through a row of holes or two rows of holes to enable easy, global comparisons among a variety of data sets. By plotting data from several film cooling studies conducted at the University of Minnesota, the dominant roles played by density ratio, hole spacing, and surface curvature become apparent. It is also seen that a slot-plate prediction/correlation from two-dimensional film cooling studies makes an excellent standard of comparison for all film cooling studies, even though the more commonly encountered (two-axis) comparisons using standardized nondimensional parameters do not usually suggest this.